Symposium 2: Student Reaction to Video-streamed Content: Does it Enhance Knowledge and Understanding? - Erskine, John; Jones, Marc (Proceedings of the International Conference on Networked Learning, 2004)
The present study examined student responses to the use of a video-streamed expert interview to improve knowledge and understanding in two key areas related to stress and sport performance. Following a series of learning activities that accompanied streamed clips, students were asked to identify what they liked best and least about the approach adopted, and state areas for improvement. A series of questions gauging reaction to both technical and pedagogical aspects of the video-streamed content was also undertaken. Overall, student responses were favourable to the use of streamed video in this context, with video streaming seen as being a more positive than negative tool in support of learning, especially in the areas of aiding clarity and understanding and presenting material in a non written format. Concerns highlighted included the non availability of text versions of the video clips and narrow access to the streamed material. The study identified areas for improvement which will allow for further development of this resource.